Of Conservation and Conservatism - Shukla, Rakesh (Indian Forester, 1996)
The paper deals with the prevalent conservatism seriously affecting wildlife conservation in the country. Despite the fact that wildlife conservation was a great success at the initial stages, serious questions are now being raised about it. A critical analysis has been done to identify the inbuilt factors in the System which are undermining the conservation efforts. These factors include - fatigued infrastructure, neglected incentives, tardy judicial proceedings, the "indispensability" syndrome, protocolized tourism and arbitrary personnel management.